Efficiency and the Role of Default When Security Markets are Incomplete - Zame, William R. (American Economic Review, 1993)
This paper argues that default plays an important positive role in the economy. If markets are incomplete and traders are only able to enter into contracts that they will be able to execute regardless of future events, contingent contracting may be severely restricted. Moreover, opening new markets may not relieve these restrictions. Default promotes efficiency in a way that opening new markets does not, by making it possible for traders to enter into contracts that they will be able to execute with high probability, but not with certainty.